A Comparison of Muscle Energy Technique (MET), Dynamic Stretching, and a Combination of Both on Cervical Pain and Range of Motion Amongst Residents of Negros Oriental: A Quasi-Experimental Study - Merquita, Beatriz; Malinao, Mary Clarence; Bautista, Lily Ann D.; Calunod, Maria Mirjana; Malicay, Jevenus; Cabarrubias, Sunday Marie; Partosa, Paul Michael; Evangelista, Johnniel S. (Silliman Journal, 2025)
Neck pain is one of the most common complaints among individuals, arising from various etiologies. Numerous techniques, such as muscle energy techniques (MET) and Dynamic Stretching (DS), have been utilized to manage neck symptoms. This quasi-experimental study compared MET, DS, and a combination of both in treating non-specific neck pain. Thirty participants from Negros Oriental were divided into three groups (MET, DS, and a combination) based on age and sex. VAS was used to measure pain, while goniometry was utilized to determine cervical lateral flexion. Results revealed that all three techniques are effective in decreasing pain and increasing lateral flexion ROM in terms of effect size after every session, but the progress every session is not enough to be considered effective according to the Minimal Detectable Change (MDC) and Minimal Clinically Important Difference (MCID). All three groups showed efficacy in treating neck pain and improving neck lateral flexion, except for VAS in the DS group, as shown by improved VAS scores and neck lateral flexion ROM measurements when pre- and post-test scores were compared. No intervention applied amongst the three groups is superior to the other.